Size and density adjustment of nanostructures in nanochannels for screening performance improvement. Issue 4 (11th January 2021) - Wang, Dagui; Cheng, Hongli; Che, Cheng; Wu, Xiaoqing; Feng, Yuezhan; Gao, Pengcheng; Xia, Fan
Abstract : Biomimetic solid-state nanochannel/nanopore with flexible geometric structures, mechanical robustness and multifunctional surfaces have attracted extensive attention in separation, catalysis, drug delivery and other fields. Abstract : Biomimetic solid-state nanochannel/nanopore with flexible geometric structures, mechanical robustness and multifunctional surfaces have attracted extensive attention in separation, catalysis, drug delivery and other fields. Nanostructures have been introduced in nanoconfines to compress substances passthrough for high-efficient screening. However, precise controls of the nanostructure's growth in nanoconfines is rare. Herein, we developed a method to control size and number density of nanoparticles in nanochannels by adjusting polydopamine reducing conditions, achieving (1) particle size increasing, density increasing; (2) particle size increasing, density decreasing; (3) particle size increasing, density invariant; (4) particle size invariant, density increasing. The nanoparticles compressed the space of functional molecules decorated on them. Increasing size and density of nanoparticle enhanced the steric hinderance of functional molecules decorated on them and improved the wetting and chirality screening through nanochannels.